The effect of brown rice flour particle size on the quality of brown rice noodles - XIONG Shaobai; YANG Xiaoli; CHEN Tingting; LUO Shunjing; LIU Chengmei (Shipin yu jixie, 2024)
ObjectiveThis study aimed to investigate the effect of brown rice particle size on the quality of brown rice noodles.MethodsBrown rice flours with average particle sizes (D[4,3]) of 370, 86, 62, 47, and 30 μm were prepared using low-temperature impact milling. Noodles were made from each flour, and their starch short-range ordered structure, crystalline structure, cooking quality, and texture properties were analyzed.ResultsBoth the short-range order and relative crystallinity of starch in brown rice noodles first increased and then decreased with decreasing particle size. Hardness and chewiness also followed this trend. Noodles prepared from flour with a moderate particle size (D[4,3] of 86 μm) showed the highest starch order, crystallinity, hardness and chewiness, indicating optimal quality.ConclusionModerate milling produces brown rice flour with an ordered structure, enhancing the hardness, chewiness and overall quality of brown rice noodles.